VILLAGE GOVERNMENT STRATEGY THROUGH DIGITAL EDUCATION TO INCREASE INFORMATION TRANSPARENCY AND DIGITALIZATION LITERACY IN FACING THE CHALLENGE OF THE DEMOGRAPHIC BONUS - Resty Dwiyanti, Andi Amytia; Syam, Anita; Irmawati, Irmawati; Mashuri, Mashuri; Andania, Ana; Anugrawati, Anugrawati (Transpublika Publisher, 2024)
The objective of this study is to inform the government about the significance of digitalization literacy and information transparency. The researcher has selected a title that emphasizes the Village Government Strategy through Digital Education to Enhance Information Transparency and Digitalization Literacy, addressing the challenges posed by the demographic bonus. The aim of this title is to equip human resources at the village level with innovative skills and prepare them for the challenges anticipated by 2045. The researcher has employed a qualitative descriptive research method, incorporating a literature review and various news reports pertinent to the Village Government Strategy through Digital Education to Enhance Information Transparency and Digitalization Literacy in addressing the demographic bonus challenges. The primary objectives of this study include providing transparent information to village communities, streamlining administrative management processes, and promoting a digital mindset and literacy among communities to foster innovation and ensure the sustainability of rural areas.